Importance of edible wild plants in world food security: The case of Turkey - Sefa Akbulut (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Production in industrial agriculture is under threat in the near future due to air pollution, excessive consumption, and climate change. Commercial production of traditional products is significant for the continuity of product diversity. Edible wild plants are usually collected from the wild and consumed for local needs. However, there are not enough initiatives for the cultivation of these plants. Turkey, which is very rich in point of biological diversity, is among the lucky countries in this regard. An important part of approximately 12000 plants in its flora is consumed as a food source by traditional methods. In this study, a list of 76 plants belonging to 34 families that are widely consumed for food purposes in Turkey is given.